Design and Fabrication of Nanostructured Electrodes for Complementary Electrochemical and Photoelectrochemical Water Splitting - Abousalem, Kholoud El Sayed (AUC Knowledge Fountain, 2022)
Designing highly active, durable, and nonprecious electrodes for overall water splitting is of urgent scientific importance to realize sustainable hydrogen production. Accordingly, the need to search efficient energy production systems is of crucial necessity. In this thesis, two various systems for sustainable hydrogen production have been reported using electrochemical and photoelectrochemical pathways. In the first part of the thesis, electrochemical water splitting involving both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) has been established. To this end, an innovative approach is demonstrated to synthesize flower-like 3D homogenous trimetallic Mn, Ni, Co phosphide catalysts directly on nickel foam via electrodeposition followed by plasma phosphidation. Moreover, the electrochemical activity of the catalysts with varying Mn: Ni: Co ratios is assessed to identify the optimal composition. The results showed that the incorporation of phosphides into the deposited components further enhanced the kinetics of both half-reactions by impeding their corrosion resistance and augmenting their long-term stability. Meanwhile, the assembled MNC-P/NF||MNC-P/NF full water electrolyzer system attains an extremely low cell voltage of 1.48 V at 10 mA/cm2. Significantly, the robust stability of the overall system results in remarkable current retention of ~96% after a continuous 50 h. While as the second part of the thesis involved designing, for the first time, two typically Nb-Zr mixed oxynitride and reduced black oxide nanotubes photoelectrodes for generating hydrogen photoelectrochemically. Ammonolysis of the nanotubes resulted in narrowing the bandgap energy from 3.23 eV to ~2.67 eV. The Nb-Zr oxynitride nanotube arrays showed approximately an enhancement of about 1900% over that reported for thin-film electrodes made of niobium oxynitride and 3700% greater than that recorded for nitrogen-doped mesoporous Nb2O5. Finally, the H2-treated nanotubes showed extraordinary stability and photoactivity upon their use for solar water splitting. This was accompanied by a noticeable reduction in the bandgap energy from 3.23 eV to 2.5 eV, which is mainly correlated with the introduced oxygen vacancies within the lattice with a remarkable conductivity. This thesis, therefore, provides a facile design and a scalable construction of superb catalysts for efficient hydrogen production systems.